Suitability of fluorescence indices for the estimation of fruit maturity compounds in tomato fruits. (21st June 2018) - Groher, Tanja; Schmittgen, Simone; Fiebig, Antje; Noga, Georg; Hunsche, Mauricio
Abstract: BACKGROUND: We examined the suitability of chlorophyll fluorescence‐based indices to monitor and predict concentrations of fruit maturity compounds during tomato ripening under different growing conditions in the greenhouse. The aim of this study was to evaluate the effects of chlorophyll concentration changes on fluorescence‐based indices and to exploit the relation between fluorescence and reflectance indices with the corresponding maturity compounds determined analytically. RESULTS: Fruits grown under water deficit matured faster than control fruits as recorded with fluorescence‐based indices. The SFR_R index correlated well with the analytical determination of chlorophyll content, whereas the single‐signal FRF_G correlated with lycopene content even if the sensor was unable to differentiate precisely between maturity stages 2 to 4. Neither the FLAV index nor the FLAV_UV index was suitable for flavonoid prediction in tomato fruits. Compared with fluorescence indices, the relation between the reflection index and pigment concentrations was lower for chlorophyll and higher for lycopene. CONCLUSION: Chlorophyll and lycopene content in tomato fruits can be estimated by means of fluorescence indices during the pre‐harvest phase. Since the chlorophyll decrease during tomato ripening is the driving force affecting all fluorescence signals, the methods are not reliable for estimation of other maturity compounds in tomato fruits. © 2018 Society of Chemical Industry